Mesenchymal Stromal Cell-Derived Microvesicles Regulate an Internal Pro-Inflammatory Program in Activated Macrophages - Henao Agudelo, Juan S.; Braga, Tarcio T.; Amano, Mariane T.; Cenedeze, Marcos A.; Cavinato, Regiane A.; Peixoto-Santos, Amandda R.; Muscará, Marcelo N.; Teixeira, Simone A.; Cruz, Mario C.; Castoldi, Angela; Sinigaglia-Coimbra, Rita; Pacheco-Silva, Alvaro; et al. (Frontiers in Immunology, 2017)
Mesenchymal stromal cells (MSCs) are multipotent cells with abilities to exert immunosuppressive response promoting tissue repair. Studies have shown that MSCs can secrete extracellular vesicles (MVs-MSCs) with similar regulatory functions to the parental cells. Furthermore, strong evidence suggesting that MVs-MSCs can modulate several immune cells (i.e. Th1, Th17 and Foxp3+ T cells). However, their precise effect on macrophages (Mɸs) remains unexplored. We investigated the immunoregulatory effect of MVs-MSCs on activated M1-Mɸs in vitro and in vivo using differentiated bone marrow Mɸs and an acute experimental model of thioglycollate-induced peritonitis, respectively. We observed that MVs-MSCs shared surface molecules with MSCs (CD44, CD105, CD90, CD73) and expressed classical microvesicle markers (Annexin V and CD9). The in vitro treatment with MVs-MSCs exerted a regulatory-like phenotype in M1-Mɸs, which showed higher CD206 level and reduced CCR7 expression. This was associated with decreased levels of inflammatory molecules (IL-1β, IL-6, NO) and increased immunoregulatory markers (IL-10 and Arginase) in M1-Mɸs. In addition, we detected that MVs-MSCs promoted the down-regulation of inflammatory miRNAs (miR-155 and miR-21), as well as its predicted target gene SOCS3 in activated M1-Mɸs. In vivo MVs-MSCs treatment reduced the Mɸs infiltrate in the peritoneal cavity inducing a M2-like regulatory phenotype in peritoneal Mɸs (higher arginase activity and reduced expression of CD86, iNOS, IFN-γ, IL-1β, TNF-α, IL-1α and IL-6 molecules). This in vivo immunomodulatory effect of MVs-MSCs on M1-Mɸs was partially associated with the up-regulation of CX3CR1 in F4/80+/Ly6C+/CCR2+ Mɸs subsets. In summary, our findings indicate that MVs-MSCs can modulate an internal program in activated Mɸs establishing an alternative regulatory-like phenotype.